The Influence Of Leadership Style And Employee Work Motivation On Employee Compliance With Job Satisfaction As An Intervening Variable In The Education Office Dairi Regency - Adi Saputra R. Purba; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
The purpose of this study is to find out and analyze the influence of Leadership Style and Motivation on Employee Compliance mediated by Job Satisfaction at the Dairi Regency Education Office. This research was carried out at the Dairi Regency Education Office. The type of research is quantitative associative. The sample in this study is 45 employees with ASN and honorary status at the Dairi Regency Education Office. The sampling technique in this study uses a saturated sample where the entire population will be a sample in this study as many as 45 people. The results of the study show that Leadership Style does not have a significant influence on Employee Compliance as shown by the T-Statistic value of 1.254 > 1.96 and the P Value of 0.210 > 0.05. In the effect of Motivation on Employee Compliance, data on T-Statistical values were obtained from 2.273 > 1.96 and P-Value values of 0.023 < 0.05 or there was an influence of Motivation on Employee Compliance. Leadership Style has a significant effect on Employee Job Satisfaction with a T-Statistic value of 3.381 > 1.96 with a P-Value of 0.001 < 0.05. Motivation has a significant effect on Employee Job Satisfaction. This can be seen from the results of the T-Statistic value of 7.026 > 1.96 with a P-Value of 0.000 < 0.05. On the effect of Job Satisfaction on Employee Compliance, a T-Statistic value of 2.215 < 1.96 was obtained with a P-Value of 0.027 < 0.05 which means that Job Satisfaction has a significant effect on Employee Compliance of the Dairi Regency Education Office. In Indirect Influence, the results show that Job Satisfaction has a role as an intervention variable in explaining the relationship between Motivation and Employee Compliance. This shows that improvements in Motivation can increase Job Satisfaction, which ultimately contributes to an increase in Employee Compliance at the Dairi Regency Education Office.